Lung function outcomes in the INPULSIS® trials of nintedanib in idiopathic pulmonary fibrosis. (January 2019) - Brown, Kevin K.; Flaherty, Kevin R.; Cottin, Vincent; Raghu, Ganesh; Inoue, Yoshikazu; Azuma, Arata; Huggins, John T.; Richeldi, Luca; Stowasser, Susanne; Stansen, Wibke; Schlenker-Herceg, Rozsa; Maher, Toby M.; et al.
Abstract: Background: In the INPULSIS ® trials, nintedanib reduced the annual rate of decline in forced vital capacity (FVC) versus placebo, consistent with slowing of disease progression. We characterised the effects of nintedanib on physiologic outcomes using pooled data from the INPULSIS ® trials. Methods: Post-hoc analyses included changes in FVC over time, cumulative distribution of patients by change in FVC % predicted, and annual rate of decline in FVC in subgroups by diffusing capacity of the lung for carbon monoxide (DLco) and composite physiologic index (CPI) at baseline. Changes from baseline in DLco and oxygen saturation by pulse oximetry (SpO2 ) were pre-specified. Results: Nintedanib significantly reduced FVC decline versus placebo from week 12. A higher proportion of patients treated with nintedanib than placebo had an improvement or no decline in FVC % predicted, whereas a smaller proportion had absolute declines in FVC ≥5% or ≥10% predicted from baseline to week 52. The effect of nintedanib on FVC decline was similar in patients with baseline DLco >40% versus ≤40% predicted or CPI ≤45 versus >45. There were no significant differences between nintedanib and placebo in change from baseline in DLco % predicted, CPI, or SpO2 at week 52. However, change (deterioration) in CPI was significantly lower with nintedanib versus placebo in patients with CPI > 45 at baseline (1.0 versus 2.9) and CPI >55 at baseline (−1.2 versus 3.3). Conclusions: A range of physiologic outcome measures in the INPULSIS ® trials support the effect of nintedanib on reducing disease progression in patients with IPF. Highlights: A range of measures support the effect of nintedanib on reducing progression of IPF. Nintedanib reduces the rate of decline in forced vital capacity. Significant differences from placebo are seen from week 12 of therapy. Nintedanib reduces the risk of absolute decline in FVC ≥10% predicted over 52 weeks. Effect of nintedanib was similar in subgroups by DLco >40% versus ≤40% predicted.